Pengaruh Permainan Menara Kubus Terhadap Perkembangan Balita Umur 14-18 bulan Di Posyandu Wilayah Puskesmas Pesantren II Kota Kediri Tahun 2015: The Effect of the Cube Tower Game on the Development of Toddlers Age 14-18 Months in the Posyandu in the Pesantren II Public Health Center in Kediri City in 2015 - Sari, Helen Puspa; Ediatmi, Ediatmi (Universitas Muhammadiyah Sidoarjo, 2016)
Various issues such as child developmental delays in motor, language, behavior, autism, and hyperactivity, in recent years is increasing, the incidence in the United States ranges from 12-16%, Thailand 24%, Argentina 22%, and Indonesia between 13% -18%. Meanwhile, as reported by the Ministry of Health of the Republic of Indonesia coverage of toddlers in the detection of growth and development of a toddler with impaired growth in Indonesia 45.7%. Pesantren Community Health Center II in Kediri in 2014, toddlers conducted early detection of growth in 2014 as many as 294 toddlers who have developmental disorders and there are 2 toddlers. The purpose of this study was to investigate the effect of a cube tower game against development in toddlers aged 14-18 months at Posyandu in Pesantren Community Health Center II region. This study included inferential research that is pre-experimental with cross sectional approach. The population in this study all toddlers aged 14-18 months in posyandu in Pesantren Community Health Center II region in kediri. The sample size used was 16 Respondents with purposive sampling technique. Based on the research results obtained by using the Wilcoxon test ρ value: 0,001 with α: 0.05 inconclusive because ρ value> α then H0 rejected H1 accepted so that it can be concluded There is the influence of the game cube tower on the development of children aged 14-8 month. The game needed to stimulate early childhood development, especially game cube tower